Anestezjologia i Intensywna Terapia Pharmacological effects of nitric oxide in extracorporeal membrane oxygenation - Taha, Rame; Blaise, Gilbert (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Nitric oxide (NO) is a gas that has potent vasodilator properties. It can be administered via inhalation in situations where NO production is impaired, and results in vasodilatation of the pulmonary capillaries. Extracorporeal membrane oxygenation (ECMO), a technique for providing life support to patients with cardiac and/or respiratory dysfunction, allows the heart and lungs to rest. Inhaled NO (INO) therapy reduces the need for ECMO in hypoxemic respiratory failure and persistent pulmonary hypertension (PPHN) in neonates; it is now the standard of care for this population. Our review will focus on the role of INO as an anti-inflammatory agent and vasodilator in various respiratory and cardiac diseases as well as its effect on the use of ECMO in term and premature infants.